2016
DOI: 10.1080/21663831.2016.1233914
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented thermal stability of inherently metastable titanium aluminum nitride by point defect engineering

Abstract: Extreme cooling rates during physical vapor deposition (PVD) allow growth of metastable phases. However, we propose that reactive PVD processes can be described by a gas-solid paraequilibrium defining chemical composition and thus point defect concentration. We show that this notion allows for point defect engineering by controlling deposition conditions. As example we demonstrate that thermal stability of metastable (Ti,Al)N x , the industrial benchmark coating for wear protection, can be increased from 800°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 69 publications
4
48
0
Order By: Relevance
“…The entire experimental details regarding thin film synthesis and ion beam analysis were reported by to Baben et al [17] and a brief summary is provided here. TiAlN thin films were grown reactively by high power pulsed magnetron sputtering [18] on sapphire substrates at a temperature of 300°C from a TiAl target.…”
Section: Experimental Details 21 Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire experimental details regarding thin film synthesis and ion beam analysis were reported by to Baben et al [17] and a brief summary is provided here. TiAlN thin films were grown reactively by high power pulsed magnetron sputtering [18] on sapphire substrates at a temperature of 300°C from a TiAl target.…”
Section: Experimental Details 21 Materialsmentioning
confidence: 99%
“…The combination of RBS and ToF-ERDA (referred to as RBS/ERDA in the following) resulted in a total measurement uncertainty of 2.5% relative deviation and the absolute composition is (Ti 0.255 Al 0.235 )(N 0.505 O 0.005 ). Moreover, the film exhibits a single phase face-centered cubic crystal structure (space group Fm3 m, NaCl prototype) [17] and a columnar growth morphology with column widths on the order of 100-200 nm [16].…”
Section: Experimental Details 21 Materialsmentioning
confidence: 99%
“…The low onset temperature for spinodal decomposition of overstoichiometric (Ti,Al)Ny is attributed to their existing metal vacancies, which enhance diffusion on the metal sublattice. 18 Diffusion requires energy to overcome the energy barriers for vacancy formation and changing atomic positions.…”
Section: B Thermal Stability Of Ti1-xalxnymentioning
confidence: 99%
“…It was shown that the onset of w-AlN phase transformation in (Ti0.52Al0.48)N0.87 occurred at about 1200 °C, 15 which is about 300 °C higher than what typically is reported for stoichiometric (Ti0.5Al0.5)N thin films. [16][17] Primary decomposition occurs on the metal sublattice and To Baben et al 18 also reports an improved thermal stability of close to stoichiometric (Ti,Al)Ny (y ≈ 1) as compared to over-stoichiometric (Ti,Al)Ny (y > 1). The faster decomposition in over-stoichiometric (y > 1)…”
Section: Introductionmentioning
confidence: 99%
“…7 In conventional dc magnetron sputter (DCMS) deposition, reported kinetic AlN solubility limits in c-(TM)1-xAlxN systems for growth temperatures Ts ~ 500 °C range from x = 0.3 for Zr1-xAlxN, 8 to 0.5 for Ti1-xAlxN, 9 and 0.67 for Cr1-xAlxN compounds, 10 with some uncertainty related to the sensitivity of the analysis method used to detect precipitation of the w-AlN phase. 11,12 Supersaturated single-phase alloys with higher Al content are typically obtained by cathodic arc deposition, with x = 0.50 for ZrAlN, 13 0.66 for TiAlN, 14,15,16 and 0.70 for CrAlN. The VAlN system is relatively less explored, with only few publications, 17,18,19 yet potentially useful predominantly due to the combination of high hardness and low friction coefficient, which makes it a promising candidate for applications as a wearresistant coating in, for example, deep drawing of high-strength steels.…”
Section: Introductionmentioning
confidence: 99%